Pengaruh Jenis Semen Portland Composite Cement dan Pozzolan Portland Cement Terhadap Faktor Konversi Kuat Tekan Beton Mutu Normal dan Tinggi - Setyatama, Mohammad Sigit; Saputra, Elvis (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2025)
With the advancement of concrete technology, including types of cement, materials, additives, test specimen shapes, and environmental conditions, the compressive strength conversion factors of concrete differ from those in PBI 1971, which is based on OPC cement. PBI 1971 does not yet account for conversion factors for high-strength concrete and requires adjustments for PCC and PPC cement. This study focuses on determining the compressive strength conversion factors for normal-strength and high-strength concrete at the ages of 3, 7, 14, 21, and 28 days using PCC and PPC cement, while also analyzing their effects on workability, compressive strength, and the rate of strength development. The research employs normal-strength concrete (25 MPa) and high-strength concrete (42 MPa) according to SNI standards, with the addition of 10% silica fume and 0.5% superplasticizer. Compressive strength tests were conducted using cylindrical specimens. The compressive strength results were modeled into regression equations, which were then used to calculate the conversion factors by dividing the average compressive strength of concrete at a specific age by the average compressive strength at 28 days.The results indicate that for normal-strength concrete, PCC cement yields higher conversion factors than PBI 1971 at 3 and 7 days, although the differences are not significant. Meanwhile, PPC cement tends to show higher values at 3 and 7 days due to its pozzolanic content. For high-strength concrete, the conversion factors for PCC and PPC cement are relatively similar to those in PBI 1971, except at 3 days, where PPC cement yields higher values. The conversion factors derived from this study are not significantly different from PBI 1971, and their application can be considered based on construction requirements, such as using PPC, PCC, or OPC cement for high early strength. PCC cement enhances workability and the rate of strength development, while PPC cement provides higher early and final compressive strength, applicable to both normal-strength and high-strength concrete.